Role of small-bowel endoscopy in the management of patients with inflammatory bowel disease: an international OMED-ECCO consensus. - Bourreille, A; Ignjatovic, A; Aabakken, L; Loftus, E; Eliakim, R; Pennazio, M; Bouhnik, Y; Seidman, E; Keuchel, M; Albert, J; Ardizzone, S; Bar-Meir, S; et al. (2009)
Crohn's disease and ulcerative colitis are lifelong diseases seen predominantly in the developed countries of the world. Whereas ulcerative colitis is a chronic inflammatory condition causing diffuse and continuous mucosal inflammation of the colon, Crohn's disease is a heterogeneous entity comprised of several different phenotypes, but can affect the entire gastrointestinal tract. A change in diagnosis from Crohn's disease to ulcerative colitis during the first year of illness occurs in about 10 % - 15 % of cases. Inflammatory bowel disease (IBD) restricted to the colon that cannot be characterized as either ulcerative colitis or Crohn's disease is termed IBD-unclassified (IBDU). The advent of capsule and both single- and double-balloon-assisted enteroscopy is revolutionizing small-bowel imaging and has major implications for diagnosis, classification, therapeutic decision making and outcomes in the management of IBD. The role of these investigations in the diagnosis and management of IBD, however, is unclear. This document sets out the current Consensus reached by a group of international experts in the fields of endoscopy and IBD at a meeting held in Brussels, 12-13th December 2008, organised jointly by the European Crohn's and Colitis Organisation (ECCO) and the Organisation Mondiale d'Endoscopie Digestive (OMED). The Consensus is grouped into seven sections: definitions and diagnosis; suspected Crohn's disease; established Crohn's disease; IBDU; ulcerative colitis (including ileal pouch-anal anastomosis [IPAA]); paediatric practice; and complications and unresolved questions. Consensus guideline statements are followed by comments on the evidence and opinion. Statements are intended to be read in context with qualifying comments and not read in isolation.